Basel Capital Requirements and Credit Crunch in the MENA Region - Ben Naceur, Sami (IMF Working Papers; Working Paper ;, 2013)
The 1988 Basel I Accord set the common requirements of bank capital to promote the soundness and stability of the international banking system. The agreement required banks to hold capital in proportion to their perceived credit risks, and this requirement may have caused a 'credit crunch,' a significant reduction in the supply of credit. We investigate the direct link between the implementation of the Basel I Accord and lending activities, using a data set spanning annual observations covering 1989-2004 for banks in Egypt, Jordan, Lebanon, Morocco, and Tunisia. The results provide clear support for a significant increase in credit growth following the implementation of capital regulations, in general. Despite higher capital adequacy ratios, banks expanded credit and asset growth. Credit growth appears to be driven by demand fluctuations attributed to real growth, cost of borrowing, and exchange rate risk. Overall, the effects of macroeconomic variables, in contrast to capital adequacy, appear to be more dominant in determining credit growth, regardless of the capital adequacy ratio, and regardless of variation across banks by nationality, ownership, and listing.